Study on thermal environment and thermal comfort in autumn season of temporary shelters in Nepal after massive earthquake 2015 - R. Thapa; H.B. Rijal (International Association of Lowland Technology, 2016)
Extreme natural disasters are events caused by environmental factors that injure, displace people and damage property. On 25th April 2015 a devastating earthquake of 7.8 on Richter scale struck Nepal causing approximately 9,000 deaths and damage to 900,000 houses. Homeless victims are doomed to live in temporary shelters. In the context of Nepal, after the massive earthquake, no research is done to evaluate the thermal environment in temporary shelters and thermal comfort of habitants. Thermal measurements and thermal comfort surveys were conducted to find out the actual conditions of thermal environment in the temporary shelter and thermal comfort status of respondents. The surveys were carried out for 30 days in autumn covering 202 residents. The mean indoor temperature is 21.1 °C, which is similar to the globe temperature. From the analysis we found that mean day time and night time indoor air temperatures are 18.7 °C and 15.2 °C respectively. The comfort temperature in the temporary shelter is 23.9 °C and the mean clothing insulations of residents is 0.73 clo. The result indicates that the indoor air temperature in the temporary shelter is considerably low in autumn season but residents are maintaining thermal comfort by using various behavioral adaptations.